Eradicating Illiteracy Through Calistung Learning and Nationalism Education at ICC Ladang Kosma - Ratih Widyawati; Fitri Nurjanah; Salistia Rohma Diyanti; Elga Dwi Yanti; Ratnasari Dyah Utami; Dian Artha Kusumaningtyas (International Conference on Education for All, 2023)
The International Partnership Community Service Learning (KKN-Dik) Activity of Muhammadiyah Aisyiyah Higher Education at ICC Ladang Kosma involves a program titled 'Illiteracy Eradication at ICC Ladang Kosma, Pahang.' In this program, we utilized a method of implementation. Firstly, we divided the learning groups into 3 categories, comprising a total of 22 students. The method employed in this research is Calistung. The results of this study demonstrate that the implementation of the Calistung teaching program significantly assisted students at ICC Ladang Kosma in comprehending the taught materials.